Pomen knjižnic pri evalvacijah in akreditacijah univerz v ZDA - Lynch, Beverly P. (Organizacija znanja, 2006)
Accreditation is an integral part of the autonomy of U.S. universities, which has changed, but also gained significance through time. Whereas the evaluationof libraries used to be based upon their size, they ar now evaluatedbased upon measures of their performance as defined by ACRL, i.e. input, output and outcome measures. A crucial part is played by library standards, whose development is closely interlinked with the process of accreditation. IFLA is constantly improving library performance measures whileputting user satisfaction first. Increasingly prominent digital formats and new ways of communication call for a new approach towards the evaluation and accreditation of libraries.
Keywords: akreditacija; evalvacija; knjižnice; knjižnični standardi; merila uspešnosti; United States of America; zadovoljstvo uporabnikov; ZDA